ANALYSIS OF THREE PROTAGONISTS CONTRIBUTING TO THE TRIVENI OF VIJAYDAN DETHA - Trivedi, Pragati (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper analyses the concept of Triveni, a term signifying the confluence of three significant elements, within the works of Vijay Dan Detha, a prominent figure in Rajasthan literature. By focusing on three distinct protagonists from his oeuvre, the study examines how each character contributes uniquely to the thematic and narrative fabric of Detha’s stories. The protagonists selected represent diverse facets of human experience and cultural reflection, serving as lenses through which Detha’s literary vision is crystallized. This paper uses a comparative analysis to reveal how these characters collectively embody the Triveni, merging individual struggles, cultural contexts, and philosophical insights. The research highlights Detha’s innovative narrative techniques and ability to weave complex, multi-dimensional characters that enrich the reader’s understanding of societal and existential themes. This paper not only enhances appreciation of Detha’s literary artistry but also contributes to broader discussions on using Triveni in narrative structures across different literary traditions.